Thermophysical features of Ellis hybrid nanofluid flow with surface-catalyzed reaction and irreversibility analysis subjected to porous cylindrical surface - Khan, Muhammad Naveed; Ahammad, N. Ameer; Ahmad, Shafiq; Elkotb, Mohamed Abdelghany; Tag-eldin, Elsayed; Guedri, Kamel; Gepreel, Khaled A.; Yassen, Mansour F. (Frontiers in Physics, 2022)
This study explores the flow irreversibility of the Ellis hybrid nanofluid (containing CoFe2O4−TiO2 nanoparticles) with homogeneous and heterogeneous reactions to a horizontal porous stretching cylinder. The energy transportation aspects are investigated in terms of the influence of joule heating and viscous dissipation. The slip and convective boundary conditions are levied on the cylindrical surface, and the mathematical flow model is transferred to a system of nonlinear ordinary differential equations using suitable transformations. The highly nonlinear systems of equations are numerically solved using the bvp4c approach in MATLAB. The graphical outcomes are obtained and discussed; it is worth noting that incremental estimations of the curvature parameter show opposite behaviors on the Ellis fluid velocity and entropy generation, i.e., the entropy generation profile increases while fluid velocity decreases. The boundary layer thinning shows resistance to impact by elasticity and magnetic field. Further, as the porosity of the liquid phase increases, the momentum of the boundary layer decreases.